Combining Pulsed and DC Gradients in a Clinical MRI-Based Microrobotic Platform to Guide Therapeutic Magnetic Agents in the Vascular Network. (11th January 2013) - Martel, Sylvain
Magnetic Resonance Navigation (MRN) relies on the use of an upgraded clinical Magnetic Resonance Imaging (MRI) scanner to navigate therapeutic, imaging, or diagnostic magnetic micro-agents in the vascular network. Although the high homogeneous field in the tunnel of the MRI scanner increases the magnetization of the navigable agents towards full saturation, the magnetic gradients superposed on such a high homogeneous field, generated by the Imaging Gradient Coils (IGC) typically used for MR-image slice selection, allow the induction of pulling forces to steer such agents in the targeted branches at the vessel's bifurcations. However, increasing the magnitude of such gradients leads to a significant decrease of the duty cycle, leading to a substantial reduction of the effective steering force being applied. To increase such a duty cycle, a Steering Gradient Coils (SGC) assembly capable of higher magnitudes while maintaining a 100% duty cycle can be installed at the cost of a much slower slew rate. Here, the use and the potential effectiveness of IGC and/or SGC for guiding such agents are briefly investigated on the basis of known specifications and experimental data.